Inside out of vertical living dimensions of resident's perception and satisfaction of living in MRB housing - Alvaro, Lemuel Jim P. (College of Architecture, University of the Philippines Diliman, 2011)
The purpose of this study is to look into the perception and satisfaction characteristics of resident's use of MRB housing among Private, Public and NGO MRB housing developments. It aims to answer the question of how residents of various MRB developments (Private, Public and NGO) compare in terms of the dimensions of perception and satisfaction characterizing their medium-rise living. The study objective are the following; 1) To compare the characteristic profile of residents of Private, Public and NGO MRB housing development. 2) To look into the perception of residents in Private, Public and NGO MRB Housing as to their feeling or level of satisfaction related to acceptability, adequacy, utilization and adaptability. 3) To describe the dimension of satisfaction of residents in private, public and NGO in relations to characteristic profile. 4) To identify problems, difficulties, concerns, issues that affect satisfaction and perception of residents in private, public and NGO housing development. 5) To infer on the implication of the findings of the study on how to improve MRB housing development. Data shall come from the following methods, FGD with housing professionals, residents' Survey Questionnaire, In-depth interview, in situ observation and desk research. Shall be descriptive using empirical data and Scoring using Likert point system, and mapping. Result finding from the overall "Feeling of Satisfaction" by type of MRB Housing initiated shows that there is no significant difference across the three sectors but majority of the all respondents (65.6 %) answered GOOD on the four level belief question namely; Excellent, Good, Fair and Poor. Conclusion from this study reveals that the level of satisfaction varies in terms of type of MRB housing sectors that a person lives. Residents of MRB units initiated by NGO have higher satisfaction in terms of comfort, living spaces, homeowners' association management, utilization of stairs inside the building and adaptability of yard and fencing outside the building. Meanwhile, MRB initiated by private developers have an edge when it comes to residents' satisfaction in terms of utilization of the laundry and storage areas, and adaptability of the entrance/exit gates, parking and multi-function hall. Consistent to their thrust, affordability seems to be a selling point of public-initiated MRB housing development.Keywords: MRB housing, Vertical living, Perception, Satisfaction, Private, Public, Non-governmental Organization.